2014
DOI: 10.1016/j.juro.2013.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation of Somatic Afferent Nerves in the Foot Increases Bladder Capacity in Healthy Human Subjects

Abstract: Foot stimulation can delay bladder filling sensations and significantly increase bladder capacity in healthy humans without overactive bladder. Although the study group was small, our results support moving forward with clinical trials of foot neuromodulation in patients with overactive bladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
2
14
1
Order By: Relevance
“…Indeed, the same mechanisms might occur in healthy humans. It has been demonstrated that transcutaneous electrical stimulation of somatic afferent nerves in the foot can delay bladder filling sensations and significantly increase bladder capacity > 50% in healthy humans, and this technology has the potential to be an effective new treatment for patients with DO [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the same mechanisms might occur in healthy humans. It has been demonstrated that transcutaneous electrical stimulation of somatic afferent nerves in the foot can delay bladder filling sensations and significantly increase bladder capacity > 50% in healthy humans, and this technology has the potential to be an effective new treatment for patients with DO [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that foot stimulation using skin surface electrodes inhibits DO and has a long-lasting effect in cats [ 2 ], likely as a result of stimulating branches of the tibial nerve in the foot. Recently, Chen [ 3 ] reported that foot stimulation can also delay the bladder filling sensation and increase bladder volume in healthy humans without OAB.…”
Section: Introductionmentioning
confidence: 99%
“…We referred a report from Dr. Chen for the stimulation method [10]. Briefly, two skin surface electrodes (LGMedSupply, Cherry Hill, New Jersey, USA) were placed over the bottom of foot and connected to a TEC Elite transcutaneous electrical nerve stimulator (LGMedSupply, New Jersey, USA) which provided constant current, rectangular pulses of 5 Hz frequency and 0.2 millisecond pulse width (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies indicate that transcutaneous stimulation of the foot can result in more than 50% increase in bladder capacity in healthy adults [10], and inhibit bladder detrusor overactivity in spinal cord-injured patients [11]. Therefore, we hypothesize that transcutaneous electrical stimulation of the foot might partially or completely relieve the symptoms caused by postoperative bladder spasms.…”
Section: Introductionmentioning
confidence: 94%
“…Experimental neuromodulation methods include (a) transcutaneous posterior tibial nerve stimulation with electrodes applied to the surface of the leg (9), (b) pudendal nerve stimulation with implanted or percutaneous electrodes (10), (c) transcutaneous foot stimulation with electrodes applied to the plantar surface (11), (d) electrical stimulation of the bladder via electrodes inserted through the urethra into the bladder lumen (12), (e) electrical stimulation of the urethra via electrodes inserted into the urethral lumen (13) and (f) electrical stimulation of the dorsal genital nerve (14,15). Sacral anterior root stimulation via permanently implanted electrodes, a technique developed by Brindley in the 1970s, is used to elicit emptying of the bladder or colon or penile erection in people with complete suprasacral spinal cord injuries (16).…”
Section: Introductionmentioning
confidence: 99%